Diagnostic and prognostic factors in patients with prostate cancer: a systematic review protocol - Mieke Van Hemelrijck; Muhammad Imran Omar; Jihong Zong; Emma Smith; Katharina Beyer; Lisa Moris; Michael Lardas; Anna Haire; Francesco Barletta; Simone Scuderi; Eleni Vradi; Giorgio Gandaglia; et al. (BMJ Open, 2021)
Introduction As part of the PIONEER (Prostate Cancer Diagnosis and Treatment Enhancement Through the Power of Big Data in Europe) Consortium, we will explore which diagnostic and prognostic factors (DPFs) are currently being researched to previously defined clinical and patient-reported outcomes for prostate cancer (PCa).Methods and analysis This research project will follow the following four steps: (1) a broad systematic literature review of DPFs for all stages of PCa, covering evidence from 2014 onwards; (2) discussion of systematic review findings by a multidisciplinary expert panel; (3) risk of bias assessment and applicability with Prediction model Risk Of Bias Assessment Tool criteria, Quality Assessment of Diagnostic Accuracy Studies (QUADAS-2) and the Quality In Prognosis Studies tool (QUIPS) and (4) additional quantitative assessments if required.Ethics and dissemination We aim to develop an online tool to present the DPFs identified in this research and make them available across all stakeholders. There are no ethical implications.